Magnitude, Symptom Presentation and Correlates of Psychological Distress Among People with Epilepsy in Southern Ethiopia: A Cross-Sectional Study - Mekuriaw B (Neuropsychiatric Disease and Treatment, 2020)
Birhanie Mekuriaw,1 Bahru Mantefardo,2 Alemayehu Molla,1 Getasew Berhanu,3 Tsegaye Mehare,4 Zelalem Belayneh1 1Department of Psychiatry, College of Health and Medical Science, Dilla University, Dilla, Ethiopia; 2Department of Internal Medicine, College of Health and Medical Science, Dilla University, Dilla, Ethiopia; 3Department of Statistics, College of Natural and Computational Science, Dilla University, Dilla, Ethiopia; 4Biomedical Department, College of Health and Medical Science, Dilla University, Dilla, EthiopiaCorrespondence: Birhanie Mekuriaw Email birhanie2013@gmail.comBackground: Psychological distress is a common co-morbid condition among people with epilepsy. Untreated comorbid psychosocial problems are associated with increased morbidity and health-care costs, and negatively affects treatment outcome of people with epilepsy. Therefore, the aim of this study was to describe the prevalence of psychological distress and to identify its associated factors among people with epilepsy attending outpatient treatment in Gedeo zone public hospitals, Southern Ethiopia.Patients and Methods: This was an institution-based cross-sectional study conducted at Gedeo zone public hospitals from July 1st to October 1st, 2019. Self-reporting questionnaire was used to screen individuals with epilepsy for the presence of co-morbid psychological distress. A face to face interview was conducted among 321 anti-epileptic medication followers. The collected data were entered into Epi-Data version 3.1 and then exported to SPSS version 20 for further analysis. Binary logistic regression was computed to identify factors associated with psychological distress. Statistically, significant association was set at p-values of < 0.05 in the final model with a corresponding 95% confidence interval.Results: The prevalence of psychological distress was found to be 38.3% with 95% CI (34.1, 42.7) among people with epilepsy attending outpatient follow-up in Gedeo zone public hospitals. Being female [OR=1.57 (95% CI: 1.01– 4.80)], uncontrolled seizures [OR=1.96 (95% CI: 1.21– 3.18)], and longer duration of illness [OR= 3.16 (95% CI: 1.75– 5.73)] were variables found to have statistically significant association with psychological distress.Conclusion: The findings of this study revealed that more than one-third of people with epilepsy screened positive for psychological distress. Therefore, this demonstrates a need to design and implement programs focusing on the prevention, early screening, and providing appropriate interventions for psychological distress among people with epilepsy.Keywords: psychological distress, mental distress, epilepsy, seizure, common mental disorder, comorbidity, Ethiopia